The Role of Preoperative Carcinoembryonic Antigen in Recurrence of Resectable Colorectal Carcinoma - Madiha Ali Khan; Rab Nawaz Maken; Hasan Nisar; Ismat Fatima; Irfan Ullah Khan; Misbah Masood; Abu Baker Shahid (Acta Clinica Croatica, 2020)
In colorectal carcinoma, carcinoembryonic antigen (CEA) is a recommended marker for surveillance after curative resection. The aim of the present study was to determine the association of preoperative CEA with recurrence of colorectal carcinoma in our population. The study included 55 patients with all operable stages of colorectal adenocarcinoma treated during the 2012-2014 period, evaluated retrospectively and followed-up for recurrence for 2 years. Data on the baseline (preoperative) CEA levels were retrieved from patient files. On data analysis, SPSS 16.0 was used. In patients with normal preoperative CEA, the rate of recurrence was significantly low (p=0.008) and the likelihood of no recurrence 1.55-fold greater as compared to patients with raised initial CEA levels (p=0.028). In patients with raised preoperative CEA, the risk of recurrence was 5.26-fold greater as compared to those with normal CEA levels (p=0.028). A significant weak positive correlation (rs=0.297) was found between raised CEA and recurrence. A highly significant (p=0.002) moderate positive correlation was recorded in patients aged <50 and moderate positive correlation of borderline significance in males (rs=0.324, p=0.058). Sensitivity was 94.4% and specificity 32.4% in predicting recurrence. Accordingly, preoperative elevated CEA showed a significant weak positive correlation with recurrence while normal preoperative CEA moderately decreased the likelihood of recurrence.